EXPERIMENTAL STUDY ON FRACTURE PERFORMANCES OF AA LY12CZ AND FSW JOINTS - ZHANG HaiYing; LIU XiuLi; ZANG WeiFeng; DONG DengKe (Jixie qiangdu)
Based on years’ experience in fracture toughness tests,the matters need attention for KRcurve and fracture toughness determination using thin compact tension（ C（ T）） specimen were studied.The KRcurve and fracture toughness of LY12 CZ alloy and friction stir welded joints were determined according to proposed test method.The microstructures of FSW joint were also observed utilizing metalloscope.The test result demonstrates that the fracture toughness of friction stir welded LY12 CZ alloy is higher than that of the parent alloy,because the weld nugget presents fine recrystallized structure.It is also found that the fracture toughnesses with crack perpendicular to rolling direction are higher than those with crack parallel to rolling direction for both welded and parent alloy.In addition,the test result indicates that the fracture toughness of C（ T） specimen is related to inplane dimension,and that the fracture toughness increases with the increase of in-plane dimension.